2014
DOI: 10.1038/cddis.2014.440
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of c-Met+ tumorigenic stromal cells of giant cell tumor of bone and targeting by cabozantinib

Abstract: Giant cell tumor of bone (GCTB) is a very rare tumor entity, which is little examined owing to the lack of established cell lines and mouse models and the restriction of available primary cell lines. The stromal cells of GCTB have been made responsible for the aggressive growth and metastasis, emphasizing the presence of a cancer stem cell population. To identify and target such tumor-initiating cells, stromal cells were isolated from eight freshly resected GCTB tissues. Tumorigenic properties were examined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 44 publications
3
14
0
Order By: Relevance
“…Stromal cells injected subcutaneously into immunocompromised mice do not produce giant cells (44)(45)(46). Moreover, tumor tissues grown on chick chorioallantoic membranes do not appear to recruit chicken monocytes to synthesize new giant cells and are unsuitable for drug administration, despite increased vascularization from the membrane, but only survive for 10 days (5,31). In our study, we used patient-derived tumor cells isolated from GCTB to establish an orthotopic murine model by intratibial injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stromal cells injected subcutaneously into immunocompromised mice do not produce giant cells (44)(45)(46). Moreover, tumor tissues grown on chick chorioallantoic membranes do not appear to recruit chicken monocytes to synthesize new giant cells and are unsuitable for drug administration, despite increased vascularization from the membrane, but only survive for 10 days (5,31). In our study, we used patient-derived tumor cells isolated from GCTB to establish an orthotopic murine model by intratibial injection.…”
Section: Discussionmentioning
confidence: 99%
“…4). The NSCs are the only proliferating population and represent the neoplastic component, which also express high concentrations of receptor activator of nuclear factor-k B ligand (RANKL), and attract and activate monocyte/ macrophage mononuclear cells to differentiate into osteoclastlike giant cells (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Wide resection gives rise to surgical complications as well as functional impairment, making the reconstruction necessary [4]. Intralesional curettage currently seems to be the mainstay of GCTB treatment, especially for tumors classified as Campanacci grade I or II [5]. How-ever, the reported local recurrence rates reach 27% to 65% in the first 2–3 years following primary surgical treatments [6].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we showed that freezing nitrogen ethanol composite treatment exhibits a comparable effect to liquid nitrogen on inhibiting neovascularization and tumor growth derived from GCT xenografts. Transplanted GCT grafts growing in chicken chorioallantoic membrane of a fertilized egg have been used as a reliable in vivo model for investigation of angiogenesis and metastasis of GCT [3,16,34,39].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the chicken chorioallantoic membrane model has been used for evaluating the efficacy of pharmacologic treatment on GCTs by determining the level of angiogenesis [32]. In the current study, we used a previously published method [3,16,32] to develop tumor nodules in the chicken chorioallantoic membrane, and then treated them with liquid nitrogen or freezing nitrogen ethanol composite. Primary GCT stromal cells were obtained from fresh tissue of five patients with GCT after institutional review board approval and written consent.…”
Section: Methodsmentioning
confidence: 99%